2018
DOI: 10.1017/s0922156518000547
|View full text |Cite
|
Sign up to set email alerts
|

Ebola and the airplane – securing mobility through regime interactions and legal adaptation

Abstract: This article concentrates on a particular controversy during the 2014 Ebola outbreak in West Africa; the mass cancellation of flights to and from affected countries. This occurred despite authoritative advice against such restrictions from the World Health Organization (WHO). During a public health emergency such as Ebola, the airplane sits at a site of regulatory uncertainty as it falls within the scope of two specialist and overlapping domains of international law; the WHO International Health Regulations (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…More recently, public health emergencies such as SARS, Ebola, and SARS-CoV-2 (Covid-19) have created potential for regulatory conflict by placing air travel within the scope of two overlapping domains of international law: the Chicago Convention, and the WHO’s International Health Regulations (IHRs) (ÓCuinn and Switzer 2019 ). Article 14 of the Chicago Convention obliges contracting states to “take effective measures to prevent the spread by means of air navigation of…communicable diseases”.…”
Section: The Global Governance Complex For International Civil Aviatimentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, public health emergencies such as SARS, Ebola, and SARS-CoV-2 (Covid-19) have created potential for regulatory conflict by placing air travel within the scope of two overlapping domains of international law: the Chicago Convention, and the WHO’s International Health Regulations (IHRs) (ÓCuinn and Switzer 2019 ). Article 14 of the Chicago Convention obliges contracting states to “take effective measures to prevent the spread by means of air navigation of…communicable diseases”.…”
Section: The Global Governance Complex For International Civil Aviatimentioning
confidence: 99%
“…Since the 1990s ICAO has been involved in international consultations to revise the WHO’s existing IHRs in light of the return of old epidemics like cholera in some parts of the world, and the emergence of new infectious diseases like Ebola. 19 In addition to consultation on policy-development, the two organizations have collaborated on practical issues such as quarantine, disinsectization of aircraft, and airport health and sanitary facilities (ÓCuinn and Switzer 2019 ). In light of growing risks of transmitting infectious agents via air-travel, ICAO in 2004 reviewed the compatibility of its aviation standards with emerging new standards for international public health and concluded that, as a result of ongoing consultations, the Chicago Convention and WHO’s IHR were “generally synergistic”.…”
Section: The Global Governance Complex For International Civil Aviatimentioning
confidence: 99%
See 3 more Smart Citations